STEM-PBL-Local Culture: Can It Improve Prospective Teachers’ Problem-solving and Creative Thinking Skills? - Woro Sumarni; Dinar Setiya Rumpaka; Sri Wardani; Sri Susilogati Sumarti (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to analyze the effect of applying problem-based learning with a STEM approach integrated with local culture (STEM-PBL-local culture) on improving creative thinking and problem-solving skills and determine the relationship between creative thinking and problem-solving skills. This research is an experimental study with a pretest-posttest non-equivalent control group design. A total of 72 prospective teachers who attended introductory chemistry courses at teacher education institutions were selected by purposive sampling. The test instrument is validated open-ended questions. Data analysis used an independent t-test. Pearson's product-moment correlation test is used to determine the relationship between problem-solving and creative thinking skills. The results show significant differences between the experimental and control groups. Students in the experimental group who received STEM-PBL-local culture experienced an improvement in creative thinking and problem-solving skills in the medium category, while the control group experienced an improvement in the low category. The Pearson product-moment correlation test shows that creative thinking and problem-solving skills have a significant relationship with a high level of correlation.